SOSIALISASI PENTINGNYA KEPATUHAN DAN KEDISIPLINAN MASYARAKAT DI ERA PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) - Ihwan Satria Lesmana; Nita Novita Sari; Rahma Diyana; Sarah Yulia Safitri; Bayu Lesmana Mulyawan (Indonesian Collaboration Journal of Community Services, 2021)
The increasing situation of the Covid-19 virus in Indonesia has prompted the government to make a new policy, namely the Enforcement of Restrictions on Community Activities. The last update was on August 11, 2021, there were 3,749,000,446 people who tested positive. The PPKM policy is one of the policies in the effort to deal with COVID-19 which does not have a clear law, because the phrase to impose restrictions on activities to control the spread of the epidemic is not contained in Law No. 6 of 2018 concerning health quarantine. The document of Law Number 6 of 2018 concerning Health Quarantine is a legal product that was separated on 7 August 2018 by President Joko Widodo. This law is a legal umbrella in supporting the government to protect the health problems of the Indonesian people from the threat of new diseases and old diseases that re-emerge. The PPKM rules made by the government have caused a lot of losses for the community, especially in the economic field where MSME activities are limited. mobile phone facilities, inadequate signal, parents who do not understand technology.